Pengaruh Penambahan Asam Asetat terhadap Sifat Fungsional Albumen Telur Itik - Imam Thohari; Firman Jaya; Nadya Arera Ritma Ajeng (Unpad Press, 2020)
The purpose of this researche was to determine the interactions of storage time and addition of acetic acid towards functional properties that were foaming ability, foaming stability, overrun, and coagulation time the egg white from duck eggs. The materials were 192 duck eggs. The method was laboratory experiment with randomized block design, two treatment factors. The first factor was storage time (T) there were 0, 7, 14, and 21 days. The second factors were addition acetic acid (P) there were 0%, 2%, 4%, and 6%, each treatment was repeated three times. The Variables foaming ability, foaming stability, overrun, and coagulation time. Data was analyzed by ANOVA and Duncan’s Multiple Range Test. The interaction storage time and acetic acid gave high significantly effect (P<0,01) on pH, foaming stability and coagulation time with the best values 87,806% (T21P4%) on foaming stability, and 52,33 second (T21P2%) on coagulation time. The interaction storage time and acetic acid on foaming ability gave significantly effect (P<0,05) with the best values 423,84% (T0P4%) and 427,59% (T21P4%) but didn’t gave significantly effect (P<0,05) on overrun. The conclusion of this researched was acetic acid could be increase functional properties the white egg from duck eggs which storage time 0, 7, 14, and 21 days.